ANALYSIS Of THE EFFECT OF ISLAMIC BANK FINANCING AND ZAKAT ON ECONOMIC GROWTH WITH POVERTY AS AN INTERVENING VARIABLE IN INDONESIA - Ade Rangga Putra Ashary; Siti Aisyah (Jurnal Ekonomi dan Manajemen, 2025)
Sharia and Zakat financing has become a very prominent trend in recent years, This can certainly be a solution in planning to alleviate poverty and increase economic growth in Indonesia. The increase in Sharia Financing and Zakat from year to year is a good situation, especially in the economic sector in Indonesia. The purpose of this study is to determine the influence of sharia financing and zakat variables on economic growth with poverty as an intervening variable. This research method uses quantitative data types processed using Amos and Eviews software. The source of this research is secondary data from monthly reports taken from the official websites of BAZNAS, OJK, and BPS. The results of the study show that the sharia financing variable has an influence on economic growth and the zakat variable also has an influence on economic growth. The sharia financing variable has no influence on poverty, but the zakat variable has an influence on the poverty variable